IMPLEMENTASI PENILAIAN OTENTIK DALAM MATA PELAJARAN BAHASA INDONESIA DI SMP NEGERI KOTA PARIAMAN - Gusriyani, Ena; Atmazaki, Atmazaki,; Abdurahman, Abdurahman (Universitas Negeri Padang, 2018)
ABSTRACTÂ The objectives of this study are three (1) to describe the types of authentic assessment used by Indonesian teachers, (2) to describe the compatibility between authentic assessment and theory in the Curriculum 2013, (3) constraints experienced by Indonesian teachers. This research type is qualitative research by using descriptive method. Data collection techniques were conducted by observation, interview, and documentation study. The results showed that teachers of SMP Negeri 1, SMP Negeri 2 and SMP Negeri 4 Pariaman have used the type of authentic assessment in the Curriculum 2013. Assessment is done through three aspects, namely attitude aspect, knowledge aspect and skill aspect.Â Kata kunci: implementasi penilaian otentik, jenis-jenis penilaian, mata pelajaran bahasa IndonesiaÂ